INFLUENCE OF NPL, BOPO, CAR, NIM AND LDR ON AUDIT OPINION (GC) WITH INTERVENING (ROA) - Syarifudin, Syarifudin (Universitas Pamulang, 2019)
This research aims to test the financial ratio as an indicator of financial soundness such as variables Non Performing Loan(NPL), Operational expense to Operational income(BOPO), Capital Adequacy Ratio(CAR), Loan to deposit Ratio(LDR),Net Interest Margin(NIM) and Return On Asset on the acceptance of going concern audit opinion. The object of this research is the banking companies listed in Indonesia Stock Exchange in 2012 - 2016. Technique sample is saturated sample.The statistical analysis use logistic regression,Linear regression,Simple linear regression and path analysis. Opinion given by the auditor is one of the considerations from auditor to indicate existence of conditions and events whether there is substantial doubt on the company's ability to survive (going concern). Opinion going concern is used as an early warning for user’s of financial statements to avoid mistakes before decide. The result of research for hypothesis 1 can be seen that Non Performing Loan(NPL) and Capital Adequacy Ratio(CAR) does not have a significant effect on Return On Asset’s, while Operational expense to Operational income(BOPO), Loan to deposit Ratio(LDR) and Net Interest Margin(NIM) have as significant effect on Return On Asset.The result of research for hypothesis II can be seen that Non Performing Loan(NPL) and Capital Adequacy Ratio(CAR), Operational expense to Operational income(BOPO), Loan to deposit Ratio(LDR) does not have a significant effect on going concern audit opinion’s, while Net Interest Margin(NIM) have as significant effect on Return On Asset on going concern audit opinion’s. and The last result of research for hypothesis III can be seen that Return On Asset have as significant effect on going concern audit opinion’s.